Marguerite de Sainte-Gemme : comédie en trois actes, en prose - Sand, George, 1804-1876 ([Paris] : Michel Lévy frères, 1859)
Item no. 1705 in Two centuries of French drama, 1760-1960, a collection of 2,014 French dramas housed in the Department of Special Collections, University of Florida Libraries.
Appears seventh in bound volume containing 51 dramas in this series.
"Représentée pour la première fois, à Paris, sur le théâtre du Gymnase, le 23 avril 1859."
Mode of access: Internet.